Human lung organoids reveal conserved CYP1A1 and metallothionein activation in response to particulate matter exposure - Seri Choi; Seung-Yeon Kim; Ji Won Baek; Won Keun Oh; Kee K. Kim; Eun-Mi Kim (Ecotoxicology and Environmental Safety)
Particulate matter (PM) poses significant adverse impacts on respiratory health, yet most studies investigating PM effects have relied on cancer-derived cell lines or animal models with limited physiological relevance to human lung tissue. To address this limitation, we developed functional lung organoids (hLOs) from human pluripotent stem cells that recapitulate the cellular complexity of human lungs for evaluating transcriptomic and toxicological responses to PM exposure. Transcriptome profiling of hLOs exposed to European Reference Material (ERM) identified 283 differentially expressed genes, predominantly enriched in xenobiotic metabolism and oxidative stress-related pathways. ERM exposure dose-dependently upregulated CYP1A1 expression and enzymatic activity while enhancing reactive oxygen species production. Comparative analysis with diesel particulate matter (DPM) treatment revealed distinct gene expression profiles but identified a conserved subset of commonly upregulated genes including CYP1A1, CYP1B1, and metallothionein family members (MT2A, MT1E, MT1G)-key regulators of xenobiotic metabolism and oxidative stress defense. Network analysis demonstrated molecular connectivity between these gene families, confirming that hLOs recapitulate metabolic and oxidative stress responses to compositionally distinct PMs. This study establishes a physiologically relevant in vitro platform for assessing pulmonary responses to environmental pollutants and identifies conserved molecular pathways activated upon PM exposure.